Writing the Argumentative Literary Review in EFL/ESL Contexts: A Critical Analysis Perspective - Bacha, Nahla Nola (International Journal for Innovation Education and Research, 2019)
Research studies have indicated that English as a Foreign/Second Language students attending English medium universities have problems in writing the literature review, an important requirement in their term and/or research papers. It has been noted that the main challenges these students face are often little or no knowledge of the task, organization and critical analysis needed. Effective literature reviews based on the western model have shown to include evaluation, clarification, integration, synthesis and organization of the controversies in past and current research on the topic being studied and identification of the gaps in the field and the question(s)/solution(s) which the researcher is attempting to address. Although much has been written on how to write literature reviews in various disciplines, there is little or none with L1 Arabic students in the Lebanese context. This paper outlines some teaching/learning guidelines of the task based on one organizational structure, the argumentative, and a critical analysis perspective to help develop these students’ skills in writing the literature review.